Spirituality Level and Quality of Life of the Elderly, Mojokerto: A Cross-Sectional Study - Andini, Dewi Intan; Hidayati, Rina Nur; Triwibowo, Heri (PT. Pubsains Nur Cendekia, 2025)
Background: Spirituality is considered an important factor influencing the quality of life of the elderly, particularly in coping with physical, psychological, social, and environmental challenges of aging. Aims: to determine the relationship between the level of spirituality and the quality of life of the elderly in UPT Pesanggrahan PMKS Majapahit, Mojokerto. Method: The research design used was analytic correlation with a cross-sectional approach. The research population was all elderly people living at the UPT Pesanggrahan PMKS Majapahit, Mojokerto, totaling 48 elderly. The sample size consisted of 42 respondents, who were selected using a purposive sampling technique. The instruments used are the Daily Spiritual Experience Scale (DSES) and the World Health Organization Quality of Life-BREF (WHOQOL-BREF). Results: The results obtained most respondents experienced a high level of spirituality, as many as 32 respondents (76.2%) experienced a high quality of life 30 respondents (71.4%). Data analysis used is Spearman's rho, which gets a significant value of p-value = 0.000 < α 0,05 with a correlation coefficient value of r = 0.760. There is a relationship between the level of spirituality and the quality of life of the elderly. Conclusion: Enhancing spirituality can significantly contribute to improving the quality of life among the elderly, particularly in the physical, psychological, social, and environmental domains. This research also presents opportunities for further exploration of the mechanisms that support or hinder the factors influencing spirituality and quality of life, as well as the development of more holistic intervention models for the elderly.